A vision of a One Health system for Australia: On the need to rethink our health system - Steele, S.G.; Toribio, Jenny-Ann; Mor, Siobhan M. (Wiley, 2022)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has clearly demonstrated our global vulnerability to emerging infectious diseases. Zoonoses — diseases that transmit from vertebrate animals to humans — are twice as likely to be implicated as emerging diseases than non-zoonoses. Such diseases have been increasingly linked to wildlife, which are a source of infection for humans and domestic animals, with viral spillover driven by human-induced changes in land use, agricultural intensification, and wildlife exploitation, among other things.3 Sadly, warnings from experts about the dangers of unsustainable development and its impact on natural systems remained largely unheeded by politicians and policymakers.